Purification, crystallization and preliminary crystallographic analysis of cytochrome P450 203A1 from Rhodopseudomonas palustris - Pang, X; Xu, F; Bell, S; Guo, D; Wong, L; Rao, Z (2007)
Cytochrome P450 enzymes constitute a large family of haemoproteins that catalyze the monooxygenation of a great variety of endogenous and exogenous organic compounds. Cytochrome P450 203A1 (CYP203A1, RPA1009) from the metabolically versatile organism Rhodopseudomonas palustris binds a broad range of substrates, in particular substituted aromatic compounds. Crystals of CYP203A1 suitable for X-ray crystallography have been obtained and diffraction data were collected in-house to 2.0 Å resolution from a single crystal. The crystals belong to space group P222, with unit-cell parameters a = 40.1, b = 95.1, c = 99.0 Å, α = β = γ = 90°. There is one protein molecule per asymmetric unit. © International Union of Crystallography 2007.